Binary response model of desire for children in Bangladesh - Sarkar, Saroje Kumar; Midi, Habshah; Imon, A. H. M. Rahmatullah (Eurojournals, 2009)
The human population growth of the last century has been truly phenomenal. The projected world population will reach 8-12 billion before the end of the 21st century (UNFPA, 1999). It is alarming for the human being. The stabilization of population will require a reduction of fertility globally. Bangladesh is the tenth most populous country in the world. The government of Bangladesh introduced population control initiative and observed the rapid fertility decline from over 6.5 births per woman to 3.1 births in the last two decades, indeed a historic record in demographic transition. However, recent statistics suggests the fertility decline in Bangladesh has stalled. It is now believed that not lack of birth control but excess desire for children is responsible for the stalled fertility rate in Bangladesh. This paper highlights some socio-economic and demographic factors, which are affecting the desire for more children. Multiple logistic regression has been used to evaluate the desire for children among the women in Bangladesh. It has been found, middle and upper class women have less desire for children than lower educated women. Therefore, in order to achieve a declined fertility rate in Bangladesh, women’s status should be enhanced through education and employment.